OCULAR SURFACE’S DISORDERS IN GLAUCOMA PATIENTS TREATED WITH LONG INSTILLATION OF BETA BLOCKERS WITH PRESERVATIVES - E. V. Varlashina; S. V. Yanchenko; S. N. Sahnov; A. V. Malyshev (Кубанский научный медицинский вестник, 2017)
The study included 30 patients with glaucomatous optic neuropathy (GON) with intraocular pressure stabilized by the instillation of b-blockers with a preservative and complaints of discomfort in the eye (1 group), 20 patients with newly diagnosed GON (2-group). Performed: a standard research; a modified morphological examination with the calculation of the mucin production factors (MPF) and tissue entropy (CHP), a multi-cytokin study of the tear liquid. 1st group patients showed signs of the syndrome of «dry eye» (SDE), including a combined lipid-, water-, mucin-deficit; epitheliopathy of conjunctiva (76,7%), conjunctiva and cornea(23,3%), marked reduction of the MPF at a moderate decrease in the number of goblet cells, and the CHP increase,  a higher level of pro-inflammatory  Th1 as well as of Th2 cytokins. The obtained data is necessary for the development of sound therapy options of the SDE of this type.